Micropropagation and shoot regeneration from leaf and nodal explants of peppermint (Mentha piperita L.) - KUKREJA, ARUN KUMAR (Journal of Spices and Aromatic Crops, 1996)
A two step procedure for in vitro plant regeneration of a commercial cultivar (MP-l) of peppermint Mentha piperita is described. Nodal explants cultured on Murashige and Skoog medium supplemented with kinetin (2-3 mgl-1) and indole-3-acetic acid (1 mgl-1) or 6-benzyl- aminopurine (2-3 mgl-1) and indole-3-acetic acid (0.25 mgl-1) produced multiple axillary and adventitious shoots which rooted on Murashige and Skoog’ medium containing 0.25 mgI-’ indole-3-acetic acid. In vitro plantlets also served as source for leaf explants. Morphogenetic responses of leaf explants were growth regulator dependent and exhibited a broad maxima over a range of growth regulator levels tested. Optimal regeneration of shoot buds was observed on Murashige and Skoog media supplemented with kinetin (3 mgl-1) and indole-3-acetic acid (1 mgl-1) or 6-benzylaminopurine (2-3 mgl-1) and indole-3-acetic acid (1 mgl-1) or a-naphthaleneacetic acid (0.25 mgl-1). These plantlets exhibited a high rate (98 per cent) of survival under glass house and field conditions.